The Role of Urinary Biomarkers as Diagnostic and Prognostic Predictors of Acute Kidney Injury Associated With Vancomycin - Sampaio de Souza Garms, Durval; Cardoso Eid, Karina Zanchetta; Burdmann, Emmanuel A.; Marçal, Lia Junqueira; Antonângelo, Leila; Santos, Adriano dos; Ponce, Daniela (Frontiers in Pharmacology, 2021)
INTRODUCTION: The incidence of acute kidney injury (AKI) related to vancomycin is variable and several risk factors related to the treatment and to patients may explain the nephrotoxicity. The role of the urinary biomarkers in AKI related to vancomycin is unknown. OBJETIVE: The aim of this study was evaluate the role of urinary IL-18, KIM-1, NGAL, TIMP-2 and IGFBP7 as predictors of diagnostic and prognostic of AKI related to vancomycin. METHODS: A prospective cohort study of patients receiving vancomycin and admitted to wards of a public university hospital from July 2019 to May 2020 was performed. We excluded patients that had AKI before starting vancomycin, hemodynamic instability, or inability to collect urine, chronic kidney disease stage 5. RESULTS: Ninety-four patients were included and the prevalence of AKI was 24.5%, while the general mortality was 8.7%. AKI occurred 11±2 days after the first vancomycin doses. The most frequent KDIGO stage was 1 (61%). There was no difference between patients who developed and did not develop AKI in gender and length of hospital stay, dose and time of use of vancomycin. Logistic regression identified as predictors of AKI, age (OR 6.6, CI 1,16-38,22, p=0.03), plasmatic vancomycin concentrations between 96-144 hours (OR 1,18, CI 1,04-1,40, p=0.04) and urinary NGAL levels between 96-144 hours (OR 1.123, CI 1.096-1.290, p=0.03). Time of vancomycin use (OR 4.61 CI 1.11-22.02 p=0.03), higher plasmatic vancomycin concentrations between 192-240 hours (OR 1.02 CI 0.98-1.06 p=0.26), and higher cell cycle arrest urinary biomarkers TIMP-2 multiplied by IGFBP-7 between 144-192 hours (OR 1.33 CI 1.10-1.62 p=0.02, OR 1.19 CI 1.09-1.39 p= 0.04, respectively) were identified as prognostic factors for non-recovery of kidney function at discharge,. CONCLUSION: AKI related to vancomycin was frequent in patients hospitalized in wards. Age, plasmatic vancomycin concentrations and NGAL between 96 and 144 hours were identified as predictors of AKI related to vancomycin use. Plasmatic vancomycin concentrations and urinary NGAL were predictors of AKI diagnosis within the next 5 days. The urinary biomarkers of cell cycle arrest TIMP-2 and IGFBP-7 and the duration of vancomycin use were associated with non-recovery of kidney function at hospital discharge moment